2002
DOI: 10.1046/j.1464-410x.2002.02787.x
|View full text |Cite
|
Sign up to set email alerts
|

Blunt renal trauma in children with previously undiagnosed pre‐existing renal lesions and guidelines for effective initial management of kidney injury

Abstract: Objectives To record pre-existing renal lesions (PERL) found incidentally during evaluation for blunt renal trauma in children, determine their importance, suggest guidelines for the effective initial management of children with significant renal trauma and to evaluate the role of temporary percutaneous nephrostomy tube drainage (TPND) in these patients. Patients and methods We reviewed 338 children who were hospitalized with blunt abdominal trauma between 1992 and 2000. Thirty-one patients had significant r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 27 publications
2
9
0
2
Order By: Relevance
“…In addition, when the causes of trauma were analysed in the present study, it was found that the most common cause was falls. Although traffic accidents have been suggested as the main cause in previously published international studies [9], falls have been the major cause in domestic studies [4,6,10,11]. As is evident in the present study, the age group most exposed to abdominal blunt trauma is the 13-18-year-olds.…”
Section: Discussionsupporting
confidence: 63%
“…In addition, when the causes of trauma were analysed in the present study, it was found that the most common cause was falls. Although traffic accidents have been suggested as the main cause in previously published international studies [9], falls have been the major cause in domestic studies [4,6,10,11]. As is evident in the present study, the age group most exposed to abdominal blunt trauma is the 13-18-year-olds.…”
Section: Discussionsupporting
confidence: 63%
“…39,53 Routine follow-up CT imaging is not advised for uncomplicated AAST Grade IIII injuries because it is not likely to change clinical management in these cases. 54-61 Routine DMSA or other functional nuclear scans are also not advised. Benefits of forgoing routine follow-up imaging in low-grade renal injuries include simplicity in follow-up, decreased radiation exposure and IV contrast complications, patient convenience, and lower cost.…”
Section: Guideline Statementsmentioning
confidence: 99%
“…The preponderance of evidence suggests that pre‐existing renal lesions increase the vulnerability of kidneys in blunt renal trauma [49–58]. There have been four studies reviewing 733 adult and paediatric patients with renal abnormalities and trauma [51,53,57,58]. In these studies pre‐existing renal abnormalities were found in 4.4–19%[58] of adult patients with blunt renal trauma.…”
Section: Pathophysiologymentioning
confidence: 99%